BORDERLINE PERSONALITY DISORDER IN DRAMA AUGUST: OSAGE COUNTY (2007) BY TRACY LETTS - Dova Yovenescha; Desvalini Anwar (Universitas Negeri Padang, 2019)
The purpose of this analysis is to expose the issue of Borderline Personality Disordere which is represented by the main character and to know the contribution of the plot, setting, and character in revealing the Borderline Personality Disorder. This analysis is related to the concept neurosis by Freud that is supported by the text-based interpretation. The result of this analysis shows the main character has Borderline Personality Disorder that can be seen from the main character’s inappropriate emotional reactions and highly self-destructive behaviors.